2018
DOI: 10.3389/fmicb.2018.01306
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Assessment of the Bioremedial Potentials of Potato Resistant Starch-Based Microencapsulated and Non-encapsulated Lactobacillus plantarum to Alleviate the Effects of Chronic Lead Toxicity

Abstract: Lead (Pb) is a well-recognized and potent heavy metal with non-biodegradable nature and can induce the oxidative stress, degenerative damages in tissues, and neural disorders. Certain lactic acid bacterial strains retain the potential to mitigate the lethal effects of Pb. The present work was carried out to assess the Pb bio-sorption and tolerance capabilities of Lactobacillus plantarum spp. Furthermore, potato resistant starch (PRS)-based microencapsulated and non-encapsulated L. plantarum KLDS 1.0344 was uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 71 publications
2
22
0
Order By: Relevance
“…Similarly, Lactobacillus rhamnosus GG encapsulation with pectin increases its viability in simulated GIT conditions. Muhammad et al (27) reported Lactobacillus plantarum KLDS 1.0344 ability to alleviate chronic lead toxicity in mice increases when encapsulated with starch originated from tomatoes (27). The study of Riaz et al (28) shows that the survival rate under simulated GIT conditions of zein-coated alginate Bifidobacterium bifidum significantly increases.…”
Section: Probiotics Encapsulationmentioning
confidence: 99%
“…Similarly, Lactobacillus rhamnosus GG encapsulation with pectin increases its viability in simulated GIT conditions. Muhammad et al (27) reported Lactobacillus plantarum KLDS 1.0344 ability to alleviate chronic lead toxicity in mice increases when encapsulated with starch originated from tomatoes (27). The study of Riaz et al (28) shows that the survival rate under simulated GIT conditions of zein-coated alginate Bifidobacterium bifidum significantly increases.…”
Section: Probiotics Encapsulationmentioning
confidence: 99%
“…When considering strains with a MIC of 34.5 ppm (for example), the Cd removal capacity ranged from 1.5% to 23.6% ( Figure S2 ). This observation suggests that metal tolerance is not a guide to metal removal, as has also been demonstrated for Pb with various L. plantarum strains [ 61 ]. Live bacteria are not necessarily required for significant metal biosorption.…”
Section: Discussionmentioning
confidence: 90%
“…The later suggests that exploring metal tolerance is not appropriate for screening purposes, as also demonstrated for lead with various L. plantarum strains [62]. The viability of bacteria is so far not necessary to allow significant metal biosorption.…”
Section: Discussionmentioning
confidence: 99%